A new combination in Helosciadium (Apiaceae) for the flora of North Africa - Stinca, Adriano; Motti, Riccardo (Phytotaxa, 2015)
According to recent molecular studies (Hardway et al. 2004, Spalik & Downie 2006, Spalik et al. 2009), the genus Helosciadium Koch (1824: 125) was segregated from Apium Linnaeus (1753: 264). The separate position of Helosciadium is supported also by morphological characters and fruit anatomy (Ronse et al. 2010).